USING OF MICRO-MOVIES FOR TEACHING CHINESE WRITING AT JUNIOR HIGH SCHOOLS IN TAIWAN - Yeh, Ron; Liu, Chih; Chung, Chih; Lou, Shi (PEOPLE: International Journal of Social Sciences, 2017)
This study is aimed to discuss the effectiveness of teaching junior high school students how to write creative Chinese composition by means of micro movies in Taiwan. In the experiment, 60 eighth-grade junior high school students in Pingtung County were recruited as participants and divided into the experiment group (31 students) and the control group (29 students). Eight teaching experiments were carried out in addition to the pre- and post- experiment tests. As suggested in the findings, by using micro-movies, the students’ writing performance was improved in terms of the content, organization, general writing rules, creative thinking and the overall scores while students’ writing motives were improved in terms of writing emotion, writing ability, writing function/utility and overall scores in the classrooms. Students in the experiment group showed greater writing performance in terms of the content, organization, general writing rules, creative thinking, and the overall scores than those in the control group. As to writing motives, significant difference was found in terms of writing emotion, writing function/efficiency and the overall scores.